Hubungan Persalinan Lama Dan Riwayat Penyakit Saat Hamil Dengan Terjadinya Komplikasi Pada Masa Nifas Di Wilayah Kerja Uptd Puskesmas Bahomotefe Kabupaten Morowali - Ernawati, Ernawati; Samsyar, Samsyar (Barongko: Jurnal Ilmu Kesehatan, 2025)
Pregnancy is a natural process that requires special attention to ensure the health of the mother and fetus. Antenatal care is very important to monitor the condition of the pregnancy and detect complications that may occur early. Prolonged labor is a term for labor that lasts longer than 24 hours in primi and more than eighteen hours in multi. The postpartum period is characterized as a very vulnerable phase because of the many risks that may arise during this period, including conditions such as anemia, pre-eclampsia/eclampsia, postpartum hemorrhage, postpartum depression, and postpartum infection. This study is a quantitative analysis, which examines the relationship between dependent and independent variables using a cross-sectional approach. Cross-sectional research is a study where the study measures independent and dependent variable data only once at a time. The results of the study based on the chi-square statistical test obtained a value of ρ = 0.000 (ρ <0.05) for Long Labor, a value of ρ = 0.001 (ρ <0.05) for History of illness during pregnancy. The conclusion is that there is a relationship between Long Labor and History of Illness during Pregnancy with the occurrence of complications during the postpartum period in the work area of ​​the Bahomotefe Health Center UPTD, Morowali Regency.